Um olhar sobre a agricultura familiar e a saúde mental através da aromaterapia - Chiappa, Rocheli Medianeira Bariani (2021)
Mental health care has never been more necessary than it is now. The COVID- 19 pandemic amplified the cases of depression and anxiety in the world. Thus, this dissertation aims to relate the use of aromatherapy as a Complementary Integrative Practice linked to the New Era, which has been using rural spaces to carry out not only the planting of bioactive plants, but also to carry out spiritual practices of connection with the earth. Considering the various functions assumed by the rural space in contemporary times, this study is pertinent given the notion of multifunctionality to weave reflections capable of assisting in a greater understanding and recreation of such spaces as a mechanism for valuing nature. In an attempt to clarify how these new views are constituted, we sought to carry out an ethnographic study, based on the use of synergy of essential oils in order to understand the therapeutic potential of essential oils, as well as to verify their use as a natural alternative in the treatment of comorbidities such as anxiety and depression combined with insertions of earth connection.